THE ROMAN IMPERIAL HOARD POTAISSA III (ROMAN DACIA) OR... WHEN WE ALL MAKE BOTH PERFORMANCE AND MISTAKES! The peculiar coins - Cristian GĂZDAC; Dan MATEI (Journal of Ancient History and Archaeology)
The present paper is dealing with the possibility offered by a Roman imperial coin hoard to discover, on one hand, the constant feature of human nature to make mistakes during working activity, and on the other hand, the fact that any new hoard may come up with new coin types or variants. The hoard Potaissa III (in Roman Dacia; nowadays, Turda, Romania) brought up various peculiar coins, that are discussed in detail here, that reveal: tricky monetary policy; engraving mistakes; engraver’s skill; new coin types; new coin type variants and post-minting human behaviour upon the coin.